Levels of Total Mercury in Cheilodactylus variegatus Valenciennes, 1833 “Pintadilla” in the coastal zone of Chorrillos-Ancon, Lima, Peru - Quintana Paetán, Sigfredo Alexander (2021)
The “Pintadilla” (Cheilodactylus variegatus Valenciennes, 1833) is a marine species that grows near the coast and is caught by artisanal fishing for human consumption. The objective of this study was to determine the concentration of mercury in this species in both muscle tissue and liver tissue. A total of 32 samples were collected, for 8 months, determining the concentration of total mercury using the cold vapor atomic absorption spectrophotometer. In general, the highest average concentration of total mercury was found in the samples collected in the Chorrillos Artisanal Fishery Market, both for muscle tissue (0.0563-0.2632 mg/kg) and for liver tissue (0.0464-0.2694 mg/kg), with respect to the Ancon Artisanal Fisheries Market, both for muscle tissue (0.0273-0.1193 mg/kg) and for liver tissue (0.0488-0.1911 mg/kg) all on a wet basis. It was observed that these results do not exceed the maximum levels allowed by the WHO (0.5 mg/kg), but it was found that there is a positive median correlation between muscle tissue and liver tissue at both sampling points.